A-160 Neuropsychiatric Symptoms in Post-Acute Sequelae of COVID-19 (PASC). (17th August 2022) - Greenfield, Melissa J; Robinson, Jamie Hansel; Wheeler, Pariya Fazeli; Shah, Udit Vipul; Vance, David E; Agnihotri, Shruti P; Kennedy, Richard; Lokken, Kristine; Gerstenecker, Kristen Triebel; Gerstenecker, Adam; Martin, Roy C; Lazar, Ronald M
Abstract: Objective: To describe psychiatric symptoms in a sample of patients seeking treatment for "brain fog" due to Post-Acute Sequelae of COVID-19 (PASC). Method: Patients were referred for a neuropsychological evaluation from the University of Alabama at Birmingham (UAB) Post-COVID Treatment Program. Ninety-two patients completed a battery of self-report questionnaires to measure mood symptoms and behavior. Patients were on average 49 years of age (range: 18 to 74), female (77%), and White/Caucasian (73%)/Black/African American (25%), with 15.49 years of education (SD = 2.43). Results: On average, patients who sought treatment for PASC reported mild to moderate anxiety (Generalized Anxiety Disorder Assessment [GAD-7]; M = 9.83, SD = 6.07), moderate depression (Patient Health Questionnaire [PHQ-8]; M = 13.23, SD = 5.81), moderate stress levels (Perceived Stress Scale [PSS]; M = 22.97, SD = 7.99). They also reported overall functional impairment in activities of daily living (Functional Assessment Questionnaire [FAQ]; M = 9.57, SD = 8.29) and perceived cognitive impairment (Cognitive Failures Questionnaire [CFQ]; M = 55.22, SD = 18.66). Additionally, patients endorsed several somatic symptoms (PHQ-15; M = 13.90, SD = 5.16), mild insomnia (Insomnia Severity Index [ISI]; M = 14.80, SD = 6.85), and severe fatigue (Chalder's Fatigue Scale [CFS]; M = 25.53, SD = 5.72). Conclusion: Patients seeking treatment for "long-COVID" report a variety of clinically significant psychiatric symptoms, suggesting the need for incorporating behavioral, lifestyle, and psychological interventions in the treatment of this population.